Integrated dynamic model of the alkaline delignification process of lignocellulosic biomass (2011)
Although in the public literature there are several studies that describe models of alkaline delignification, they were originallydeveloped for the paper industry, and do not include the effects of important operating variables such as temperature, hydroxide-ionconcentration, solid to liquid weight ratio, particle size, biomass composition (hemicellulose, lignin fraction) and mixing. This lack of detailed models of the pretreatment stages prompted the current study that describes a model which includes the variables listed above and provides an important tool for predicting the degree of lignin removal in lignocellulosic materials such as sugarcane bagasse (Saccharum officinarum L). The model considers kinetic expressions available in the literature. The kinetic parameters were determined by fitting the model to experimental data obtained for that purpose in our lab. The experimental matrix considered eighteen, 24-h isothermal experiments in which bulk and residual delignification stages were observed to occur in a parallel manner. Carbohydrate removal and hydroxide consumption were related to lignin removal by effective stoichiometric coefficients that were calculated by fitting the experimental data. A mixing compartment network model that represented mixing inside the reactor was included into a temporal superstructure based on the similarity between plug flow reactors and ideal batch reactors to model a non-ideally mixed batch reactor. The kinetic model was validated with data obtained in this study.